제2 언어 교실에서 학습자 모국어의 효용 - 협동적 과제 수행을 중심으로 = The efficacy of learners` first language in the collaborative interactions of the Korean Classrooms - Ryoo, Agnes Hye Jin 류혜진 (2020)
The use of the first language (L1) in the second language (L2) classroom remains a controversial issue in communicative language teaching approaches. Although the first language has been widely used as a cognitive or communicative tool in the second language classroom interaction, its importance or function has been rather ignored or undervalued or even sanctioned in the discussion. This study aims to find a way to utilize or foster the first language by affirmatively understanding its existence and efficacy. It is hoped to enable learners’ merit of using the first language to be optimized by investigating the purpose and context of the first language use in language learning. The experiment shows that the use of first language has been decreased in higher level interactions and cognitively less demanding tasks and the purpose and aspects of the first language use varies depending on the characteristics of tasks given to students. This study will conclude that the first language plays a role as an tool for learning not an obstacle in the second language classroom and be followed by investigating its pedagogical implications.